Trends of basal cell carcinoma at the Centre of Dermatovenereology of Vilnius University - Jurčiukonytė, Ramunė; Stundys, Domantas; Gylienė, Iveta; Grigaitienė, Jūratė; Bylaitė-Bučinskienė, Matilda (Acta medica Lituanica, 2019)
Introduction and objectives. Basal cell carcinoma is the most common locally invasive malignant epidermal neoplasm in humans and its incidence has increased over the last decades worldwide, especially among the Caucasian population. Basal cell carcinoma accounts for about 75% of all skin cancers. Incidence data on basal cell carcinoma is sparse because traditional cancer registries often do not register these tumours. In Lithuania, patients with skin cancer and melanoma were traditionally treated in centralized oncological institutes. From 2006, the Centre of Dermatovenereology at Vilnius University Hospital Santaros Klinikos (Vilnius, Lithuania) provides modern diagnostic and treatment facilities to oncodermatological patients. The objective of the study was to evaluate epidemiological and clinical data of basal cell carcinoma at the Centre of Dermatovenereology during the last 15 years. Materials and methods. Medical documentation of the cases of histologically-proven basal cell carcinoma diagnosed between 2000 and 2015 was analyzed. Epidemiological and clinical evaluation according to the patients’ age, sex, and place of residence, as well as tumour localization, its histological type, and treatment options was performed. Results. After the skin lesion biopsy and histopathological examination, a total of 847 basal cell carcinomas were confirmed to 782 patients. During the study period, the total annual number of newly diagnosed basal cell carcinomas rose steadily in our centre: 2.7% between 2000 and 2003, 6.5% between 2004 and 2006, 13.6% between 2007 and 2009, 27.6% between 2010 and 2012, and 49.6% between 2013 and 2015. The biggest part of patients (28.4%) were 70–79 years old, 4.6% – younger than 40, 7.3% – 40–49, 17.1% – 50–59, 27.2% – 60–69, 14.1% – 80–89, and 1.3% ≥90 years old. The average patient age was 66.0 (±13.6). Of these patients, 62.0% were female and 38.0% male; 63.6% were from the capital city, 18.3% from other cities, and 18.2% from rural areas. Basal cell carcinomas occurred most often in the face region 49.0%, followed by the trunk – 29.4%, the scalp and neck – 10.9%, arms and legs – 7.7%, in 2.9% location was not specified and the whole body – 0.1%. The predominant histological type of basal cell carcinomas was nodular (60.6%), other diagnosed types were superficial (22.9%), infiltrative/morpheaform (8.0%), mixed nodular and infiltrative (1.7%), pigmented (0.2%), rare types (micronodular, infundibulocystic, ductal and mixed) – 0.6%; the type was not specified in 6.0% of cases. Nodular, superficial, and infiltrative types were the most common morphological types in all body sites: respectively, in the face – 67.5%, 12.5%, 9.4%; in the scalp and neck region – 77.2%, 14.1%, 5.4%; in the trunk – 49.8%, 37.3%, 7.2%; in extremities – 41.5%, 43.1%, 7.7%. The nodular type was more common among the elderly and its incidence increased with age (p = 0.009), meanwhile, superficial basal cell carcinomas prevailed among younger patients (